International legal solution to the problems of climate change and sustainable development - M., Sylkina S.; J., Altayeva K. (Farabi Journal of Social Sciences, 2019)
In the article are researched the main problems in the field of protection of the environment and steady development. Are analysed international treaties and other documents in this field, national ecological legislation, and the role of international organisations. In the modern world, in spite of emergence a lot of common views of the ecological problems and measures taken by the parties of international law, is continuing the deterioration of the condition of the environment, which threatens the welfare of people, and in some cases – and the existence of life on planet. Abidance of the quality standarts of the environment are becoming one of the most key parameters of the competitiveness of states. Adapting optimal international legal regime of its protection and application of taken decisions depend on political will, on functioning and development of the hard system of cooperation, based on international treaties and including states, international organisations, governmental and non-governmental organisations. The Secretary-General of the UN Ban Ki-moon has designated the fighting with the climat change as a moral and practical imperative of our time. The problems of saving auspicious environment and steady usage of resources are closely related with social requirements, demographic pressing and poverty in developing countries, contrary to excessive and often wasteful examples of consumption in developed countries. Searching for acceptable solutions of ecological problems with considering needs of developing countries, using different way for making obligations, when developed countries are capable of taking for themselves more strict obligations on provision of auspicious quality of global environment, is important. Especially keenly is being felt the need of achievement of universal participation in international treaties of the UN, their equable interpretation and implementation, in general the need of careful attitude to legal instruments in the sphere of protection of the environment and created regimes. It has become obvious that further economic development of humanity, directed to the growth of people’s welfare in combinated with the social guarantees becomes possible only in frames of «ecologically steady development». Suitable legal rules, and economic instruments, accepted either on national, and on international level, could have provided the equality between economic growth, increasing of production of material goods and saving of the environment. Key words: environment, international treaty, states, global organizations, climate change, steady development, mechanism of interstate cooperation, climatic system, the atmosphere, greenhouse gases, the framework strategy, energy sources, Framework Convention, ratification, implementation, UN, legal obligations, The Kyoto protocol, energy saving, world community.